Efficacy and cost-effectiveness of two online interventions for children and adolescents at risk for depression (E.motion trial): study protocol for a randomized controlled trial within the ProHEAD consortium - Baldofski, Sabrina; Bauer, Stephanie; Bilić, Sally Sophie; Kaess, Michael; Moessner, Markus; Salize, Hans Joachim; Voss, Elke (Trials, 2019)
Depression is a serious mental health problem and is common in children and adolescents. Online interventions are promising in overcoming the widespread undertreatment of depression and in improving the help-seeking behavior in children and adolescents.